Комплексный подход по формированию технического облика силовой установки, интегрируемой в планер, при синтезе летательного аппарата - Логинов, В. В. (НТУ "ХПИ", 2009)
A comprehensive approach and methods for forming the technical appearance of the power device integrated into the frame in the course of military and transportation aircraft synthesis have been developed. A method to assess the technical excellence level for aircrafts by the degree of their efficiency has been developed. The article also describes solutions for real tasks emerging when the excellence level for aircrafts is substantiated by the degree of their efficiency. It also discloses the results of comprehensive analytical and experimental studies based on the developed research and methodic approach to the comprehensive method of parametric integration for major aircraft subsystems. The developed comprehensive approach makes it possible to forecast integrative properties of an aircraft at the early design stages and can be applied to other technical systems such as “mobile platform – power device.”
Keywords: летательный аппарат; военная авиация; самолет; силовая установка; планер; аэродинамика